Treatment outcome in early diffuse cutaneous systemic sclerosis: the European Scleroderma Observational Study (ESOS). Issue 7 (10th February 2017) - Herrick, Ariane L; Pan, Xiaoyan; Peytrignet, Sébastien; Lunt, Mark; Hesselstrand, Roger; Mouthon, Luc; Silman, Alan; Brown, Edith; Czirják, László; Distler, Jörg H W; Distler, Oliver; Fligelstone, Kim; et al.
Abstract : Objectives: The rarity of early diffuse cutaneous systemic sclerosis (dcSSc) makes randomised controlled trials very difficult. We aimed to use an observational approach to compare effectiveness of currently used treatment approaches. Methods: This was a prospective, observational cohort study of early dcSSc (within three years of onset of skin thickening). Clinicians selected one of four protocols for each patient: methotrexate, mycophenolate mofetil (MMF), cyclophosphamide or 'no immunosuppressant'. Patients were assessed three-monthly for up to 24 months. The primary outcome was the change in modified Rodnan skin score (mRSS). Confounding by indication at baseline was accounted for using inverse probability of treatment (IPT) weights. As a secondary outcome, an IPT-weighted Cox model was used to test for differences in survival. Results: Of 326 patients recruited from 50 centres, 65 were prescribed methotrexate, 118 MMF, 87 cyclophosphamide and 56 no immunosuppressant. 276 (84.7%) patients completed 12 and 234 (71.7%) 24 months follow-up (or reached last visit date). There were statistically significant reductions in mRSS at 12 months in all groups: −4.0 (−5.2 to −2.7) units for methotrexate, −4.1 (−5.3 to −2.9) for MMF, −3.3 (−4.9 to −1.7) for cyclophosphamide and −2.2 (−4.0 to −0.3) for no immunosuppressant (p value for between-group differences=0.346). There were no statistically significant differences in survival between protocols before (p=0.389) or after weighting (p=0.440), but survival was poorest in the no immunosuppressant group (84.0%) at 24 months. Conclusions: These findings may support using immunosuppressants for early dcSSc but suggest that overall benefit is modest over 12 months and that better treatments are needed. Trial registration number: NCT02339441.